Family Influence and Firm Performance: The Mediating Role of Stewardship - Alves, Catarina Afonso (2020)
Purpose— This study examines how stewardship might mediate the influence of family ownership on firm financial performance. We argue that differences in financial performance may reflect not only the family’s influence but also the prevalence of a stewardship-oriented culture, across varying degrees of family influence. Design/methodology/approach—The measure of family influence uses the F-PEC scale: family [F], power [P], experience [E], and culture [C]. It supports cross-firm comparisons of different levels of family influence. To capture the multidimensional nature of family influence, this study uses structural equation modelling and measures the meditating effects of stewardship. Findings—The results reveal a mediating effect of stewardship; family firms achieve better performance when they take advantage of and encourage stewardship attitudes among owners and leaders. Factors associated with stewardship behaviour, including stewardship motivation and stewardship culture, help explain why some family firms perform better than others. Practical implications—When analysing the behaviour of family firms, interested entrepreneurs, managers, and consultants should acknowledge that the family’s influence entails both financial and emotional capital. The survival of the family businesses depends on balancing these aspects. Originality—In response to calls for research into mediators of the complex relationship between family influence and firm outcomes, this study provides a novel explanation for performance-maximizing behaviours by organizations, in which pro-organizational attitudes coexist with self-serving motives.